Exploring the nexus of artificial intelligence, fake news and defense strategy - Rafsanjani, Wildan Akbar Hashemi; Risma Sarah, Herlina Juni; Saputro, Guntur Eko; Simbolon, Luhut (Bricolage : Jurnal Magister Ilmu Komunikasi, 2025)
The advancement of artificial intelligence (AI) has significantly impacted digital communication, including the creation and dissemination of disinformation. Technologies such as deepfakes, chatbots powered by natural language processing (NLP), and generative algorithms enable the production of false information that is challenging to distinguish from reality, posing a threat to information security and global stability. In the defense context, AI-driven disinformation can be weaponized in information warfare, undermining public trust, creating social disorientation, and weakening national security strategies. This study examines how AI is utilized to spread disinformation and its implications for defense strategies. Through case studies and literature analysis, the research highlights the urgent need for robust mitigation measures, including the development of AI-based detection technologies, the enhancement of digital literacy, and global collaboration in regulating the use of AI. The findings offer insights into the strategic threats posed by AI to defense systems, while providing recommendations to strengthen resilience against AI-driven disinformation attacks.